Drought tolerant maize for Africa project - Shaw, Alison; Kristjanson, Patricia M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Context: Up to 65% of arable land in Africa is dedicated to maize production. It is a major commodity and source of food yet the constraint is drought, disease and weeds. The project is trying to make 100 varieties of maize in Africa that we are trying to make drought tolerant. Gender has become an important issue for helping the least privileged groups. Other differentiations such as level of education and wealth are important as well.